Analisis SWOT Dalam Meningkatkan Daya Saing Perguruan Tinggi Keislaman - Kurniadi, Moch. Danu (STAI Ali bin Abi Thalib Surabaya, 2025)
This research was conducted to analyze the strategic position and formulate strategies to enhance the competitiveness of STAI Ali Bin Abi Thalib Surabaya through a SWOT approach. The background of this study is based on the importance of competitiveness among Islamic higher education institutions amidst the challenges of globalization and inter-institutional competition. The purpose of this research is to identify the strengths, weaknesses, opportunities, and threats faced by the institution, as well as to develop relevant strategies to sustainably improve competitiveness. This study employs a descriptive quantitative approach. Data were collected through questionnaires distributed to lecturers, educational staff, and students as respondents. The data were analyzed using descriptive statistical methods and the construction of IFAS and EFAS matrices based on the weight and rating of each SWOT factor. The findings show that STAI Ali Bin Abi Thalib Surabaya possesses significant internal strengths, such as the quality of its Arabic language program, distinctive scientific methodology, and competent human resources. On the other hand, external opportunities, such as society’s growing interest in Islamic education and potential strategic partnerships, also support the institution’s development. The strategic position of STAI is located in Quadrant I, which indicates that a growth strategy is the primary choice. The implication of this research is that the institution needs to focus on strengthening differentiation and developing flagship programs based on internal strengths and external opportunities.